Petrophysical Study and Rock Type Determination of Siliciclastic Reservoir: Case Study Sand of Bekasap Formation, AF Field, Central Sumatra Basin, Indonesia - Dwi Charisah Andriyani; Sarju Winardi; Sugeng Sapto Surjono (Geological Engineering Department Universitas Gadjah Mada, 2022)
An integrated subsurface study has been performed for a large and mature field at the Bekasap Formation in Central Sumatra Basin. The Bekasap Formation sand represents an undeveloped reservoir because of its heterogeneity. There are five sand reservoirs (BK1, BK2, BK3, BK4, and BK5) from Bekasap Formation, which each zone or layer bounded by a flooding surface. Each sand reservoir has particular characterization based on petrophysical properties that represent geological process. The petrophysical properties consist of shale volume, porosity, and water saturation obtained by wireline log calculation. This study uses conventional core data to validate the log calculation to achieve an accurate interpretation. Bekasap reservoir is a sandstone reservoir deposited in an estuarine with tide-dominated. Formation evaluation was done to determine the interest zone by petrophysical properties. The result well-log calculation and reservoir cut-offs showed the thickest reservoir in the BK 3 with the best average values of petrophysical properties with an average shale volume 0.32; porosity of 0.245. Otherwise, in rock type determination, four lithofacies are divided in the reservoir based on flow units. The sample RT 1 and RT2 provided the best reservoir zones with HFU1 and HFU2. The RT 3 and RT 4 dominated in HFU3 and HFU4 had the lowest potential zones of reservoir. The final findings showed a good correlation between sedimentologic analysis and petrophysical properties in the rock type determination. As a result, the best reservoir quality development is controlled by the depositional environment (texture and structure) rather than the diagenetic process in this reservoir. It is proven by petrophysical properties in BK1, and BK2 is coastal barrier sand (tidal sand bar) has more clean sand rather than in BK3 and BK4 deposited in the offshore bar.